(untitled) (Malaysian Journal of Civil Engineering, 2018)
The current techniques reinforcing earth levees in the Mekong Delta have been less effective. The soil cement deep mixing technology (SCDM) using a small light weight equipment system has high potential to reinforce earth levees effectively and sustainably due to utilization of the in-situ soils. This paper investigated characteristics of field soilcrete created by a small light weight equipment system known as the NSV system in Dong Thap province which is one of thirteen provinces in the Mekong Delta. A 30-m soilcrete wall was completely constructed using the NSV in Dong Thap province. A 0.5-m thick wall of single row soilcrete columns and a 1-m thick wall of double row soilcrete columns with a depth of 8 m were built in 15 m long. Unconfined compressive strength test (UCS) was employed to determine the strength and stiffness of soilcrete specimens. About 60 soilcrete specimens were successfully made and tested using a UCS instrument in laboratory. Unconfined compressive strength, qu, inside a soilcrete column was higher than those of the designed strength about 4 to 5 times. The qu of 2-column overlapped locations was higher than those of inside columns about 1.6 to 2.5 times. The qu of 3-column overlapped locations was lower than those of inside columns about 1.4 to 1.6 times. Ratio of secant modulus of elasticity to UCS is about 28 to 140 times.